2020
DOI: 10.1101/2020.09.04.283077
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improvements to the ARTIC multiplex PCR method for SARS-CoV-2 genome sequencing using nanopore

Abstract: Genome sequencing has been widely deployed to study the evolution of SARS-CoV-2 with more than 90,000 genome sequences uploaded to the GISAID database. We published a method for SARS-CoV-2 genome sequencing (https://www.protocols.io/view/ncov-2019-sequencing-protocol-bbmuik6w) online on January 22, 2020. This approach has rapidly become the most popular method for sequencing SARS-CoV-2 due to its simplicity and cost-effectiveness. Here we present improvements to the original protocol: i) an updated primer sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
381
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(404 citation statements)
references
References 34 publications
3
381
0
2
Order By: Relevance
“…The authors of the preprint, Vanaerschot et al noted that SNVs could impact assay accuracy if diagnostic primers and probes are also being used to quantify viral loads in patients. We found that at least 10 other primer pairs could potentially be at risk in different geographical regions due to SNVs that appear proximal to the 3’ ends of primers ( Figure 3B–K ): China-CDC-N-F and R; NIH, Thailand, WH-NIC N-F; US CDC 2019-nCoV-N1-R; US CDC 2019-nCoV-N2-F; ARTIC-V3_nCoV-2019_11_RIGHT; ARTIC-V3_nCoV-2019_13_LEFT; ARTIC-V3_nCoV-2019_34_LEFT; ARTIC-V3_nCoV-2019_39_LEFT (note that the ARTIC primers are used for nanopore sequencing; Tyson et al, 2020 ); WHO N_Sarbarco_R1; and Institut Pasteur, Paris 12759Rv. Labs and clinics can use COVID-19 CG ( https://covidcg.org ) to check their most commonly used primers and probes against the SARS-CoV-2 sequences that are prevalent in their geographical regions.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of the preprint, Vanaerschot et al noted that SNVs could impact assay accuracy if diagnostic primers and probes are also being used to quantify viral loads in patients. We found that at least 10 other primer pairs could potentially be at risk in different geographical regions due to SNVs that appear proximal to the 3’ ends of primers ( Figure 3B–K ): China-CDC-N-F and R; NIH, Thailand, WH-NIC N-F; US CDC 2019-nCoV-N1-R; US CDC 2019-nCoV-N2-F; ARTIC-V3_nCoV-2019_11_RIGHT; ARTIC-V3_nCoV-2019_13_LEFT; ARTIC-V3_nCoV-2019_34_LEFT; ARTIC-V3_nCoV-2019_39_LEFT (note that the ARTIC primers are used for nanopore sequencing; Tyson et al, 2020 ); WHO N_Sarbarco_R1; and Institut Pasteur, Paris 12759Rv. Labs and clinics can use COVID-19 CG ( https://covidcg.org ) to check their most commonly used primers and probes against the SARS-CoV-2 sequences that are prevalent in their geographical regions.…”
Section: Resultsmentioning
confidence: 99%
“…30 RNA samples from nasal swabs and bronchoalveolar lavage at day 3 and 5 were selected for sequencing. cDNA and multiplex PCR reactions were prepared following the ARTIC SARS-CoV-2 sequencing protocol v2 (Tyson et al, 2020). The inoculum was also sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…10 RNA samples from nasopharyngeal swabs at day 3 post-exposure were selected for sequencing along with the inoculum. cDNA and multiplex PCR reactions were prepared following the ARTIC SARS-CoV-2 sequencing protocol v2 49 . V3 primer scheme Ther., therapeutic.…”
Section: Viral Sequencingmentioning
confidence: 99%